La ricezione degli elfi nella letteratura tedesca (1740-1830) - Laura Gherardini (Filologia Germanica, 2024)
From the eighteenth century onwards, German literature shows the revival and reworking of severalelements of the Middle Ages. This interesting phenomenon, which partly provides an answer to the claim of national German identity and is encouraged by cultural excitement involving all forms of artistic expression, gives rise to outstanding literary works. The reminiscence of the past involves themes, events, pre-Christian legends, even creatures of the Nordic mythology such as the elves, which are, however, perceived through folklore filters and, therefore, multicultural traditions. This paper aims at investigating the way in which elves and their literary role are represented by German authors from the first half of the eighteenth century to the first years of the nineteenth. A short excursus about the information which can be obtained by Old English and Old Norse literature is provided, in order to consider what characteristics have been preserved and which have been changed in folk tales and superstitions. Part of the analysis is dedicated to linguistic aspects, due to the fact that German authors adopt the loan word Elf, Elfen instead of using the local expression. The German tale Die Elfen by Tieck has been analysed, considering that in this work elves play an important role in the chain of events. It is suggested that the elf Zerina could be seen as the key figure responsible for the breakdown of the fragile balance between the real and the fairy world.